2015
DOI: 10.1002/vipr.201500571
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Calculation Of Slot Channels with Variable Cross Section

Abstract: The range of operation pressures of non‐contact vacuum pumps may reach six decades, and flow regime in slot channels of the rotor mechanism may vary from molecular flow to viscous flow. This article is a continuation of a series of authors‘ publications dedicated to the development of a method which makes it possible to calculate promptly the conductance of slot channels with complex contoured geometry with the minimal clearance at a certain point along gas flow direction for all three gas flow regimes: molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…At low pressures pump characteristics are mainly influenced by backward flow through channels in rotor mechanism. That is why articles [14,15] covering study of such channels conductance are of considerable interest. Profile effectiveness is considered from the viewpoint of channels conductance decrease in [15][16][17].…”
Section: Zusammenfassungmentioning
confidence: 99%
See 1 more Smart Citation
“…At low pressures pump characteristics are mainly influenced by backward flow through channels in rotor mechanism. That is why articles [14,15] covering study of such channels conductance are of considerable interest. Profile effectiveness is considered from the viewpoint of channels conductance decrease in [15][16][17].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…That is why articles [14,15] covering study of such channels conductance are of considerable interest. Profile effectiveness is considered from the viewpoint of channels conductance decrease in [15][16][17]. It was showed that minimum backward flow through inter-rotor channel is obtained for elliptical profile with b/a ≈ 0.84 ÷ 0.86 and r/a = 0.610 ÷ 0.64 in free molecular flow regime.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…It is very important to calculate the conductance of the rotor mechanism slot channels exactly, because pumping characteristics of any non-contact pump depend on backward flow [7]. That is why a lot of papers concerning development of calculation methods are devoted to study of pumps slot channels conductance [8,9].…”
Section: Introductionmentioning
confidence: 99%